Using eye tracking to evaluate the usability of the new improved online performance management system at the University of the Free State - Brown, Ronald William (University of the Free State, 2015)
Performance management is a very important aspect of any modern organisation and the systems used to conduct performance management need to be well-designed and “easy to use”. This study was conducted in order to evaluate the usability of the online performance management system (PMS) of the University of the Free State (UFS). The usability of any system is based on three components, namely effectiveness, efficiency and satisfaction. This research study followed a blended design that consisted of questionnaires and eye tracking tests. The population consisted of support staff and line managers at the UFS and a sample of 20 participants were chosen through nonprobability, purposive sampling. Of the 20 participants, 12 were line managers and the remaining 8 were members of the support staff. Furthermore, a group of three power users were identified and used as a benchmark. These power users are staff members who make use of the online PMS on a daily basis. All participants were given a series of tasks to complete on a demo version of the online PMS. In order to analyse the eye tracking data, each task had to be divided into scenes and areas of interest were drawn on each scene. The time to first fixation and the time to first mouse click were analysed for each of the areas of interest. The data from the questionnaires indicated that the majority of participants used the online PMS only once or twice a year. There was a clear difference in the time it took participants to complete each task and the time it took the power users to complete each task. The power users understood the system because they use it on a daily basis, while the other participants struggled to identify the necessary steps to complete each task. The online PMS of the UFS has low levels of usability and this study recommended a number of changes with regard to the design of the online PMS of the UFS. It is the hope of the researcher that these recommendations will contribute to improving the online PMS of the UFS.
Dissertation (MBA (Business Administration))--University of the Free State, 2015
Keywords: Performance management; Eye tracking; Usability; User experience; Human resources; Online systems